Morphology of the eye and free neuromast of larval ayu and pale chub and its relation to behaviour in water flow - Kawamura, Gunzo; Mukai, Yukinori; Ohta, Hiroyuki (Japanese Society of Fisheries Science, 1983)
While ayu Plecoglossus altivelis and pale chub Zacco platypus lay their eggs on spawning beds with similar conditions in water flow and bottom sediments in rivers, the former achieves downstream migration after hatching and the latter remains in the river after its emergence from the spawning bed. To find out a possible explanation for these markedly different behaviour patterns of the larvae, the eye and neuromast which are important sensory organs in rheotaxis were examined morphologically. Upon hatching, the larval ayu already have morphologically well-developed free neuromasts with cupula and eyes with pure cone retina while the larval pale chub have no developed sensory organds. Thereafter, the eyes and neuromasts of the latter developed fast, and upon its emergence from the spawning bed and exposure to water flow at 4 days old, these sensory organs have already developed almost as well as those of ayu. Both sensory organs of these two larvae were considered functional enough to enable the larvae to respond to water flow visually and mechanically. Therefore, it is suggested that there might be an active behavioural process governing the downward migration of the ayu, such as a choice of downward water flow or an active downward swimming.